Stimulation of hair regrowth in an animal model of androgenic alopecia using 2-deoxy-D-ribose - Anjum, Muhammad Awais; Zulfiqar, Saima; Chaudhary, Aqif Anwar; Rehman, Ihtesham Ur; Bullock, Anthony J.; Yar, Muhammad; MacNeil, Sheila (Frontiers in Pharmacology, 2024)
Androgenetic alopecia (AGA) affects both males and females worldwide. New blood vessel formation can restore blood supply to stimulate the hair regrowth cycle. Recently, our group reported that 2-deoxy-Dribose (2dDR) is 80 to 90% as effective as VEGF in the stimulation of neovascularization in in vitro models and in a chick bioassay. . In this study we aimed to assess the effect of 2dDR on hair growth. We prepared an alginate gel containing 2dDR, polypropylene glycol and phenoxyethanol. The AGA was developed in C57BL6 mice by injecting testosterone (TE) intraperitoneally. A dihydroxy testosterone (DHT) treated group was used as a negative control, a Minoxidil group was used as a positive control, and we the study included groups treated with 2dDR gel and a combination of 2dDR and Minoxidil. Each treatment was applied for 20 days. Minoxidil and 2dDR gel treated groups both stimulated hair growth morphogenesis. H&E stained skin sections of C57BL/6 mice demonstrated an increase in length, diameter, hair follicle Formatted: Font: (Default) Times New Roman, Bold density, anagen/telogen ratio, diameter of hair follicles, area of hair bulb covered in melanin, and an increase in the number of blood vessels. Masson's trichrome staining showed an increase in hair bulb area covered in melanin. The effects of the FDA approved drug (Minoxidil) on hair growth were similar to that of 2dDR (80 to 90%). There was no significant benefit seen by combining Minoxidil with 2dDR. We conclude that 2dDR gel has potential for the treatment of androgenic alopecia and possibly other alopecia situations where remains the stimulation of hair regrowth is desirable -such as after chemotherapy. The mechanism of activity of 2dDR remains to be established.